The Role of Information Sharing and Trust on Supply Chain Performance among Culinary MSMEs in Palu City - Stiven Thomas; Fatlina Zainuddin; Asngadi Asngadi; Kadek Agus Dwiwijaya (Journal of Economics and Management Scienties, 2026)
Supply chain performance remains a challenge for culinary MSMEs due to limited information sharing and trust among supply chain partners. This study aims to analyze the effect of information sharing and trust on supply chain performance among culinary MSMEs in Palu City using a quantitative approach. Primary data were collected from 60 owners and employees of culinary MSMEs through questionnaires, with respondents selected using non-probability purposive sampling, and analyzed using SPSS version 30.0. The results show that information sharing and trust individually have a positive and significant effect on supply chain performance, and simultaneously both variables also significantly influence the supply chain performance of culinary MSMEs in Palu City. These findings provide important practical implications for regional economic growth and MSME development, as strengthening information sharing and trust can enhance supply chain performance and support the formulation of sustainable economic development strategies. The novelty of this study lies in its specific focus on culinary MSMEs within the accommodation and food service provision sector, which has distinctive operational characteristics, thereby offering more contextual empirical evidence on the role of information sharing and trust in improving supply chain performance compared to prior studies that largely focused on large firms or MSMEs in general.